Bentuk tajuk nama: perubahan-perubahan di dalam katalog-katalog Perpustakaan Universiti Malaya - Chuah, M. (University of Malaya Library, 1983)
Before 1982, description of items in the University of Malaya Library card catalogues was done in accordance with rules secified in the first edition of the Anglo America Cataloguing Rules with some local modifications. However, with effect from 1st January 1982, the main author-title and subject catalogue were closed. Records of new items are processed in MALMAC format and maintained in microfiche format. Aso, the Library has decided to adopt the new Anglo American cataloguing rules edition 2. The new headings formulated will be in the form most likely to be known to readers, that is the form most commonly appearing in wrks and citations. Consequently, some headings in the card catalogue will be in conflict with thise in the COM catalogue.